2005
DOI: 10.3844/ajidsp.2005.107.110
|View full text |Cite
|
Sign up to set email alerts
|

Review of Pasteurella multocida Infections over a Twelve-Year Period in a Tertiary Care Hospital

Abstract: Abstract:The aim of this study was to present the epidemiological, clinical and microbiological data, as well as the management and the outcome of 13 patients with documented Pasteurella multocida infections, diagnosed in the University hospital of Crete, Greece, between 1993 and 2004. Most patients (62%) were >70 years of age. Respiratory tract infections were most commonly encountered (61.5%), followed by soft-tissue infections (30.8%) and septicemia (7.7 %). Underlying diseases included malignancies, bullou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In patients with an impaired immune system, the initially localized infection appears to easily disseminate and affect the meninges [11][12][13]15] via bacteremia, as described in the present case.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In patients with an impaired immune system, the initially localized infection appears to easily disseminate and affect the meninges [11][12][13]15] via bacteremia, as described in the present case.…”
Section: Discussionmentioning
confidence: 63%
“…Localized infections are the best known manifestations of human infections. However, the respiratory tract is the most common site in P. multocida infections unrelated to traumatic animal contact [11]. Infections of the central nervous system have been reported only infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…Christidou et al reported in their study that two patients died after developing acute respiratory syndrome (ARDS) from P. multocida pneumonia. The third patient who initially presented with intracranial hemorrhage requiring craniotomy also died of P. multocida pneumonia [17]. …”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, another route of transmission could simply be through respiratory secretions from dogs licking the patient’s face which would facilitate mucous membrane colonisation, with no evidence of an animal bite or scratch 10. This could have caused secondary bacteraemia and overwhelming sepsis 7 , 10 , 12…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice for P multocida is penicillin G. Other penicillins with good activity against P multocida include ampicillin, penicillin VK and amoxicillin 14. Amoxicillin–clavulanic acid has excellent in vitro activity8 and in a study of 13 different human P multocida isolates 100%, showed cefuroxime susceptibility although this is not the treatment of choice 12. For penicillin allergic patients, chloramphenicol can be used 8.…”
Section: Discussionmentioning
confidence: 99%